Effect of potassium combined with organic fertilizers on growth, yield and sweetness of corn planted on bris soil - Athirah Amran (Universiti Malaysia Sabah, 2018)
This study was conducted to determine the effect of potassium combined with organic fertilizers on the growth, yield and sweetness of reddish waxy corn. The experiment was arranged on Completely Randomized Design (CRD) covering a span of three months. The treatments were: control or 60 kg ha-1 of potassium (Tl), 30 kg ha-1 potassium + 20 tons ha-1 chicken manure biochar + 1.5 tons ha-1 of bokashi (T2), 90 kg ha-1 potassium + 20 tons ha-1 chicken manure biochar + 1.5 tons ha-1 of bokashi (T3) and 120 kg ha-1 potassium + 20 tons ha-1 chicken manure biochar + 1.5 tons ha-1 of bokashi (T4). Each treatment was replicated six times. Stem girth, number of leaves, height of first cob, fresh weight of first cob, 100 grains weight, cob girth, cob length and sweetness of Brix reading was analysed using ANOVA at 5% significant levels. Least Significant Different (LSD) was used to compare the means for significantly different results. Significant differences on growth was obtained at (p<0.05) in waxy corn for the number of leaves, height of first cob, length of cob and girth of between the control and all treatments. However, no significant difference was obtained for sweetness of waxy corn for all treatments. Mean total for growth parameters; number of leaves, stem girth and height of first cob from soil surfaces and mean total for yield parameters; cob girth, length of cob, fresh weight of cob, 100 grains weight and number of kernels was significantly higher for all treatments of T2, T3 and T4 compared to control treatment of Tl. Results of the study showed no significant different on the sweetness of waxy corn with increasing potassium application resulting in increased total soluble content. Similar studies for different rate of organic fertilizers and soil analysis can be done to further ascertain the effects on growth, yield and sweetness parameters of reddish waxy corn with selected soil properties.